Trailblazing Person‐Centred Care: Lessons From a Hospital Cluster‐Wide Retreat to Co‐Design Approaches to Person‐Centred Care in Singapore. - Meng, Xiankun; Tan, Amanda Wei Li; Koh, Samantha Shi Man; Ng, Shanice Shi Hui; Puteh, Balkhis; Lee, Chien Earn; Lim, Esther Li Ping; Low, Luke Sher Guan; Teo, Stephanie Swee Hong; Sim, Andy Gim Hong (Health Expectations, 2026)
Introduction: Person‐centred care (PCC) is globally recognised as essential for quality healthcare, yet implementation remains inconsistent in Singapore due to hierarchical structures, time constraints, and fragmented understanding. SingHealth, Singapore's largest public healthcare cluster, initiated a retreat to co‐design a unified approach to PCC across its institutions. Objectives: The retreat aimed to (1) align stakeholders on PCC's importance; (2) co‐develop a locally tailored PCC definition; (3) advance PCC through five workstreams (user experience, research, education, service innovation, strategic partnerships); and (4) provide experiential co‐design learning. Methods: This qualitative case study employed reflexive thematic analysis to analyse data from a retreat designed using Goffman's frame analysis. The retreat engaged 42 healthcare practitioners, 26 senior management, and 13 patient/caregiver experience experts in a three‐phase co‐design process. 1. Pre‐design: Strategic stakeholder invitation and pre‐reading to align perspectives. 2. Generative phase: Creative methods ('Frozen' metaphors, flip cube exercises and patient videos) to explore PCC's 'what' and 'why', followed by live visual scribing, discussion and presentation. 3. Evaluative phase: Visioning exercises, debates on patient autonomy, and development of an implementation matrix. Results: Four key themes emerged:. 1. Shared responsibility between patients and providers. 2. Communication skills as foundational to PCC. 3. Integration of PCC into systems and culture. 4. Actionable steps, including patient‐reported experience measures and new models of care. Tangible outputs included a shared vision‐ 'Empowering individuals. Everyone matters' and a five‐level implementation matrix operationalising PCC at institutional, departmental, and patient‐provider levels. Conclusion: The retreat successfully fostered stakeholder alignment and co‐designed actionable strategies for PCC. The co‐design process successfully revealed nuanced tensions around shared responsibility while generating implementable strategies. This model demonstrates how structured stakeholder engagement can advance PCC in hierarchical healthcare systems. Patient or Public Contribution: Experience experts (patients and caregivers), constituting 16% of retreat participants, were strategically recruited from established networks. They actively co‐designed the PCC definition, participated in world café discussions, informed implementation strategies across five workstreams, co‐created the vision statement and validated the final implementation matrix. Their lived experiences critically shaped key themes of this event. One experience expert co‐authored this manuscript, reflecting sustained partnership.